2015
DOI: 10.1007/s00167-015-3705-6
|View full text |Cite
|
Sign up to set email alerts
|

Multiple PRP injections are more effective than single injections and hyaluronic acid in knees with early osteoarthritis: a randomized, double-blind, placebo-controlled trial

Abstract: I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
333
2
15

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 321 publications
(354 citation statements)
references
References 33 publications
4
333
2
15
Order By: Relevance
“…Indeed, at least from the owners’ HCPI score side, the results could be attributed to a placebo effect. However, a number of randomized, controlled trials demonstrated variable efficacy of the major treatments (HA, PRP, or NSAIDS) in both dogs and humans . Furthermore, we have additional unpublished data regarding the use of bone marrow‐derived MSCS in dogs affected by spontaneous OA where, despite good clinical results, extended culture time, the need for specialized facilities, and high‐costs make it more limited compared to MFAT.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, at least from the owners’ HCPI score side, the results could be attributed to a placebo effect. However, a number of randomized, controlled trials demonstrated variable efficacy of the major treatments (HA, PRP, or NSAIDS) in both dogs and humans . Furthermore, we have additional unpublished data regarding the use of bone marrow‐derived MSCS in dogs affected by spontaneous OA where, despite good clinical results, extended culture time, the need for specialized facilities, and high‐costs make it more limited compared to MFAT.…”
Section: Discussionmentioning
confidence: 99%
“…Although a previous study has reported the direct effects of various drugs and PRP on knee osteoarthritis, it is essential to investigate the overall role of PRP in affecting the entire joint cytokine homeostasis (37). PRP has a long half-life and therefore is beneficial for treatment of knee osteoarthritis as PRP may be expected to degrade slowly (32).…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, al llevar estas recomendaciones a la práctica clínica, debemos tener en cuenta que estos pueden generar eventos adversos potenciales que limitan su uso (7,8), principalmente en pacientes con patología cardiovascular, gastrointestinal, hepática y metabólica (8) y, por otro lado, la efectividad del acetaminofén para el manejo sintomático de la OA ha quedado cuestionada en un metanálisis reciente presentado por Bruno y cols. (9).…”
Section: Introductionunclassified
“…(9). Por su parte, los medicamentos tópicos (sin un efecto sistémico) juegan un papel importante y son ampliamente usados para el manejo a corto plazo, pero no son efectivos en OA severa (7). La capsaicina tópica tiene un nivel de evidencia tipo 1B con un número necesario a tratar (NNT) de 8 en su presentación al 0,025 % (10).…”
Section: Introductionunclassified
See 1 more Smart Citation